Correction: Electro-organic synthesis: an environmentally benign alternative for heterocycle synthesis. Issue 34 (19th August 2022) - Devi, Suman; Jyoti,; Kiran,; Wadhwa, Deepak; Sindhu, Jayant
Abstract : Correction for 'Electro-organic synthesis: an environmentally benign alternative for heterocycle synthesis' by Suman Devi, et al., Org. Biomol. Chem., 2022, 20, 5163–5229.